Oskar and the eight blessings (Roaring Brook Press, 2015)
A refugee seeking sanctuary from the horrors of Kristallnacht, Oskar arrives by ship in New York City with only a photograph and an address for an aunt he has never met. It is both the seventh day of Hanukkah and Christmas Eve, 1938. As Oskar walks the length of Manhattan, from the Battery to his new home in the north of the city, he passes experiences the city's many holiday sights, and encounters it various residents. Each offers Oskar a small act of kindness, welcoming him to the city and helping him on his way to a new life in the new world. This is a heartwarming, timeless picture book.